The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/nu15040872
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Obesity Effect of Auricularia delicate Involves Intestinal-Microbiota-Mediated Oxidative Stress Regulation in High-Fat-Diet-Fed Mice

Abstract: Auricularia delicate (ADe), an edible fungus belonging to the family Auriculariaceae and order Auriculariales, possesses antimicrobial, hepatoprotective, and antioxidant effects. In this study, after systematic analysis of its composition, ADe was administered to high-fat-diet (HFD)-fed mice to investigate its anti-obesity effect. ADe significantly controlled body weight; alleviated hepatic steatosis and adipocyte hypertrophy; reduced aspartate aminotransferase, total cholesterol, insulin, and resistin; and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
1
0
Order By: Relevance
“…On the other hand, some authors attributed metabolic deregulations and oxidative stress to changes in the intestinal microbiota composition caused by high-fat or high-fructose diets. Thus, ameliorative effects could be related to the prebiotic character of some polyphenols [ 42 , 43 , 44 ]. In fact, in a previous study, chia defatted flour showed positive effects on the intestinal microbiota using an in vitro gastrointestinal digestion model (increasing Lactobacillus and decreasing Enterobacteriaceae ) [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some authors attributed metabolic deregulations and oxidative stress to changes in the intestinal microbiota composition caused by high-fat or high-fructose diets. Thus, ameliorative effects could be related to the prebiotic character of some polyphenols [ 42 , 43 , 44 ]. In fact, in a previous study, chia defatted flour showed positive effects on the intestinal microbiota using an in vitro gastrointestinal digestion model (increasing Lactobacillus and decreasing Enterobacteriaceae ) [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serum total cholesterol (TC) levels and triglyceride (TG) were measured using assays kits BC1985 and BC0625 acquired from Solarbio Company (Beijing, China) according to the methods of [28,29], following the manufacturer's protocols. The method of [30] was followed to assess the serum HDL-C (high-density lipoprotein cholesterol) levels, while the other lipid parameters, such as LDL-C (high-density lipoprotein cholesterol) and very LDL-C, were mathematically considered following the technique depicted by [31].…”
Section: Lipid Profile Assessmentmentioning
confidence: 99%
“…In vitro studies have shown that ADe polysaccharide effectively scavenges ROS, highlighting its antioxidative effects [27]. Our previous investigation revealed that ADe can exert anti-obesity effects in mice fed with high-fat diets by modulating oxidative stress [28]. However, the inhibitory effect of ADe on CAC, along with a lack of comprehensive understanding of underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%